Mental Health Literacy for Teenagers through Interactive Education in Schools - Irmayani, Irmayani; Ginting, Rosita; Bangun, Sri Melda; Samura, Jul Asdar Putra; Ginting, Luci Riani; Surya Darma (JURNAL PENGMAS KESTRA (JPK), 2025)
Adolescent mental health is an important aspect in optimal growth and development, but mental health literacy among students is still low. This community service activity aims to improve students' mental health literacy through interactive education at SMA Muhammadiyah 16 Lubuk Pakam. The method used is a participatory education approach with a combination of pretest-posttest, discussion, games, and educational videos. The activity was carried out in May 2025 involving 30 grade XI students who were selected purposively. The pretest results showed that only 33% of students had a good understanding of mental health. After the intervention, there was a significant increase, with 90% of students reaching the "good" category and the average score increasing from 39.6 to 92.0. Qualitative evaluation showed that 83% of students felt better able to recognize symptoms of stress, and 70% were interested in forming regular discussion groups. This activity also encouraged students' openness to counseling and received appreciation from the school. The discussion emphasized that interactive-based education is effective in increasing understanding and positive attitudes towards mental health. However, the limited duration of the activity is an obstacle in deepening the material. Therefore, it is recommended that similar programs be conducted periodically and integrated into the school guidance and counseling system through peer counselor training and mental health clubs. Overall, this educational approach proves that schools can be a strategic place to build psychological literacy in adolescents systematically and sustainably.